Appreciating networked learning: Value creation in practice - van Amersfoort, Daniel L.; Nijland, Femke J.; de Laat, Maarten (Proceedings of the International Conference on Networked Learning, 2012)
In recent years an extensive body of research has emerged that focuses on concepts describing how teacher learning can be embedded in daily practice. This includes professional development initiatives that promote the use of social networks to support teacher learning. These networks, also referred to as learning networks, offer opportunities for teachers to expand their knowledge potential in an informal setting. However, researchers and school management alike, find it hard to grasp the implicit learning outcomes created within these learning networks. It is therefore difficult to appreciate, assess and share the value that is created beyond the boundaries of the network itself. With our poster we will present a framework for assessing and promoting value creation in learning networks, which was developed by Wenger, Trayner & De Laat (2011). It departs from a perspective in which learning is seen as a process of value creation that is a result of participating in social networks. To appreciate the richness of the value created in learning networks, the framework proposes five different cycles in which value is created through networked learning activity: 'immediate value', 'potential value', 'applied value', 'realized value', and 'reframing value'. By telling value creation stories, the value that is created through each of these cycles can be articulated. Our research focuses on two possible applications of the value creation perspective. The first possible application is in educational practice, where we focus on three distinct uses: first, we aim to study how the framework facilitates the articulation of value creation, second, we aim to study its use for assessing and appreciating networked learning outcomes within organizations, and third, we aim to study the potential of the value creation cycles in guiding networked learning activities. The second possible application is to use the framework as a research instrument, in which we focus on exploring the extent to which the different value creation cycles occur in practice. The question central to our studies into this matter is whether the value creation cycles cover all value that is created within learning networks and by assessing the value that is actually created in learning networks.